Exploration of Invasive Alien Plant Species on Habitat of Rhino in Icharni, Chitwan National Park, Nepal - Bist, Birendra Bahadur; Adhikari, Ram Chandra (The Journal of Knowledge and Innovation, 2023)
The study was conducted with main purpose to assess the floral diversity and explore invasive species on rhinoceros habitat in two different research sites with in Chitwan National Park. The rhino is placed in the list of endangered species by International Union for Conservation of Nature and highly threatened due to loss their habitat by rapidly increasing invasive species. The study was done for a period of one month in (September to October) 2020. The 10 m, 5 m, and 1 m radius circular quadrates were utilized to gather data on trees, shrubs, and herbs, respectively. A total of 25 plant species were recorded from 15 plots. The importance values of each species of trees were analyzed. Seven species of invasive types were recoded from 15 plots (10 plots from riverine forest and 5 plots from grassland). Mikania micrantha was most dominant species with IVI 103.02 followed by Pogostemon benghalensis with IVI 78.93 and Chromolaena odorata with IVI 34.57 as the second and third most dominant invasive species respectively. The conclusion is that invasive species have an impact on the grassland and riverine forest, which are needed by the mega herbivore. The management of rhino habitat and the preservation of the rhino population are seriously threatened.